Clinical Analysis, Drug Designing And QSAR Studies On Rheumatoid Arthritis - D.S.V.G.K.KALADHAR; K.V.V.V.SATYANARAYANA; A. KRISHNA CHAITANYA; S. A. K. ZAKIR HUSSAIN (International Journal of Pharma and Bio Sciences, 2010)
The clinical data related to Rheumatoid Arthritis has shown that there is more number of males (60%) than females (40%) during January month at KGH, Visakhapatnam, India. The patients also have more number of Neutrophils (72%) and Lymphocytes (18%) and less number of Eosinophils (10%) and Monocytes (0%) suffering from Rheumatoid Arthritis. Based on docking results Leflunomide and Desoxycorticosterone Pivalate shown good results based on distance approach (43.5) against RA. Based on Emin values, Auranofin (-66.73) has shown good activity compared with other selected drugs. Based on QSAR analysis Cyclosporine and Phenacetin are related and also shown similar results with docking.